Outcome for children with cyclical vomiting syndrome. Issue 11 (22nd June 2007) - Fitzpatrick, E; Bourke, B; Drumm, B; Rowland, M
Abstract : Objective: Cyclical vomiting syndrome (CVS) is a disorder that carries a significant burden of disease for children and their families. The aim of this study was to examine the outcome of a group of children diagnosed with CVS from 1993 to 2003. Methods: Children diagnosed with CVS over a 10-year period were identified and a review of the clinical records was carried out to define demographic features and the spectrum of disease at presentation. The patient's parent was contacted to establish the child's current well-being. Ethical approval for the study was obtained. Results: Fifty one children were diagnosed with CVS and 41 agreed to participate in follow-up. Mean age was 5.8 (SD 3.3) years at onset of CVS, 8.2 (SD 3.5) years at diagnosis, and 12.8 (SD 4.8) years at follow-up. Vomiting had resolved at the time of follow-up in 25/41 (61%) children. Sixteen of 41 (39%) children reported resolution of symptoms either immediately or within weeks of diagnosis. However, a large number of children from the group whose vomiting resolved and the group that were still vomiting continued to have somatic symptoms, with 42% of children suffering regular headaches and 37% having abdominal pain. 32 (78%) parents felt that the provision of a positive diagnosis and information made a significant impact on the severity of vomiting. Conclusions: While 60% of children with CVS have resolution of symptoms, a significant proportion of both those in whom symptoms have resolved and those in whom vomiting persists continue to suffer from other somatic symptoms.